Types of Faculty Incivility as Viewed by Students in Bachelor of Science in Nursing Programs. - Holtz, Heidi Kathleen; Rawl, Susan M.; Draucker, Claire (Nursing Education Perspectives (Wolters Kluwer Health))
BACKGROUND Faculty incivility can negatively affect student learning outcomes and safe clinical performance, yet little is known about the types of faculty incivility experienced by students. AIM The aim of this qualitative descriptive study was to describe common types of incidents of faculty incivility as reported by students enrolled in traditional bachelor of science in nursing programs. MEHTOD Qualitative descriptive methods were used to analyze the narratives of 30 students who had experienced incidents of faculty incivility. RESULTS A typology explicating the different ways students perceive faculty to be uncivil included six categories: judging or labeling students, impeding student progress, picking on students, putting students on the spot, withholding instruction, and forcing students into no-win situations. CONCLUSION Nursing faculty and administrators can use the incident typology to guide discussions related to detecting, assessing, and preventing incivility in nursing education.